2006
DOI: 10.1124/dmd.105.007872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Herbal Extracts on the Function of Human Organic Anion-Transporting Polypeptide Oatp-B

Abstract: ABSTRACT:Most known interactions between herbal extracts and drugs involve the inhibition of drug-metabolizing enzymes, but little is yet known about the possible role of transporters in these interactions. In this study, we have examined the effects of herbal extracts used in dietary supplements on the function of organic aniontransporting polypeptide B (OATP-B; OATP2B1), which is expressed on human intestinal epithelial cells and is considered to be involved in the intestinal absorption of various drugs. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 35 publications
(40 reference statements)
7
62
1
2
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 21 Our data are in line with a previous publication showing that Ginkgo leaf extracts and quercetin-3-glucoside, quercetin-3-rutinoside, kaempferol-3-glucoside, and kaempferol-3-rutinoside inhibited the OATP2B1-mediated transport of estrone-3-sulfate in HEK293-cells stably expressing OATP2B1 [18].…”
Section: Page 21 Of 37supporting
confidence: 81%
See 3 more Smart Citations
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 21 Our data are in line with a previous publication showing that Ginkgo leaf extracts and quercetin-3-glucoside, quercetin-3-rutinoside, kaempferol-3-glucoside, and kaempferol-3-rutinoside inhibited the OATP2B1-mediated transport of estrone-3-sulfate in HEK293-cells stably expressing OATP2B1 [18].…”
Section: Page 21 Of 37supporting
confidence: 81%
“…However, it is not stated whether fexofenadine (120 mg) and Ginkgo biloba extract (120 mg) were given simultaneously. Therefore, it could be speculated that the lack of significance is caused by a non simultaneous administration of Ginkgo biloba extract and fexofenadine.Page 21 of 37A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 21 Our data are in line with a previous publication showing that Ginkgo leaf extracts and quercetin-3-glucoside, quercetin-3-rutinoside, kaempferol-3-glucoside, and kaempferol-3-rutinoside inhibited the OATP2B1-mediated transport of estrone-3-sulfate in HEK293-cells stably expressing OATP2B1 [18].In the present study we also established HEK293 cells stably expressing OATP1A2. In previous studies investigating the function of OATP1A2, Xenopus laevis oocytes or Hela cells transiently expressing OATP1A2 were used [10][11].…”
supporting
confidence: 81%
See 2 more Smart Citations
“…In vivo studies showed that grapefruit, orange, and apple juices greatly reduced the plasma concentration of aliskiren, probably by inhibiting its OATP2B1-mediated influx in the small intestine (Tapaninen et al, 2010(Tapaninen et al, , 2011. Fuchikami et al (2006) showed that some herbal extracts used in dietary supplements significantly inhibited the function of OATP2B1, suggesting that co-administration of some dietary supplements might decrease the absorption of orally administered substrates of OATP2B1. Roth et al (2011) reported that green tea catechins epicatechin gallate and epigallocatechin gallate significantly inhibited OATP2B1-mediated E3S uptake.…”
Section: Introductionmentioning
confidence: 99%